Redefining marginality on Italian Apennines: An approach to reconsider the notion of basic needs in low density territories - Vendemmia, Bruna; Lanza, Giovanni (REGION, 2022)
The concept of basic needs and essential services evolves according to sociocultural parameters. Therefore, defining marginality based on the distance from a predefined set of services, institutionally considered essential for life, may lead to an unfocused representation of marginal and more fragile areas. This work focuses on a territory located on the Apennine of the Province of Piacenza, northern Italy. These mountainous areas are characterized by significant shrinking processes, ageing population, low income and educational rate, unemployment, and by work/study-related mobility practices over long distances and at high speed, revealing low levels of attractivity and significant dependence on more dynamic areas of the region. Moreover, according to the National Italian Strategy for Inner Areas, they have been identified as inner areas because of the high distance from main services. Starting from quantitative research based on availability, location, and accessibility to a set of services considered essential, the present work aims to reconsider and integrate this desk-based approach with an on-site qualitative survey, thanks to interviews with inhabitants and persons with special knowledge of the territory as well as participant observation. The hypothesis is that, particularly in low density and peripheral areas, a mixed-methods research methodology that includes the accounts of populations and local stakeholders may help to extend the knowledge of their actual needs and their willingness to travel, thus reconsidering their accessibility to what they perceive as essential services and, consequently, redefining the notion of marginal and fragile territories.